Does political uncertainty influence firm owners` business perceptions? - Marina Riem (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
Using microdata that serve as the foundation of the ifo Business Climate Index, Germany's leading business cycle indicator, I examine whether political uncertainty influences how firm owners perceive their present state and future development of business. I use state election months as indicators of times of high political uncertainty. The results show that firm owners are optimistic regarding their expected business development before state elections. After state elections firms change their expectations and expect their business to develop worse. It is conceivable that firm owners are more optimistic prior to state elections because politicians promised individual policies to gratify the firms' needs during election times. Firms might be disappointed after elections as the promises made during election campaigns by politicians turn out to be empty words.
Keywords: C23; D22; D72; H32; H70; 330; Business perceptions; political uncertainty; elections; survey data; panel data